Severe malocclusion and oral health-related quality of life in adolescents aged 12-15 years - Cibele da Cruz Prates OLIVEIRA; Marijara Vieira de Sousa OLIVEIRA; Carlos Antônio Amaro LIRA; Niely Enetice de Sousa CATÃO; Luana de Carvalho LOURENÇO; Rebecca Durand Garrido RAMALHO; Alessandro Leite CAVALCANTI; Alidianne Fábia Cabral CAVALCANTI (Dental Press Journal of Orthodontics)
ABSTRACT Introduction: Malocclusion is a public health problem. The evidence of its impact on quality of life is contradictory and requires further studies. Objective: The aim of this study was to estimate the prevalence of severe malocclusion and its impact on oral health-related quality of life in schoolchildren aged 12-15 years. Methods: A cross-sectional study was conducted with a probabilistic sample of 391 students. A sociodemographic questionnaire was used to collect information regarding the family context. The presence of malocclusion was assessed using the Dental Aesthetic Index (DAI), and oral health-related quality of life (OHRQoL) was analyzed using the Oral Health Impact Profile (OHIP). A descriptive and bivariate analysis of data was carried out. Multivariate Poisson regression models were used. The significance level adopted was 5%. Results: The prevalence of severe malocclusion was 37.6%, being 8.4% higher in the group aged 12-13 years (95%CI=1.48-2.29; p=0.034); and 11.2% higher (95%CI %=1.43-2.06; p=0.020) among those who perceived that their teeth were poorly positioned. Severe malocclusion was not associated with OHRQoL (p=0.686). Conclusions: The psychological discomfort, social disability and psychological disability domains had a negative impact on OHRQoL. However, there was no negative impact of severe malocclusion on OHRQoL.